Biological Safety Evaluation of 99mTc-DTPA-Ketoconazole for Diagnosis of Fungal Infection - Maula Eka Sriyani; Hendris Wongso; Eva Maria Widyasari; Rizky Juwita Sugiharti; Iim Halimah; Iswahyudi Iswahyudi; Ahmad Sidik; Epy Isabela; Witri Nuraeni (Indonesian Journal of Physics and Nuclear Applications, 2017)
Infectious diseases have become one of the leading cause of mortality around the world, including in the Southeast Asia. One of the microbial that cause infection is fungi. Occasionally, deep-seated fungal infection is difficult to detect using conventional diagnosis methods and therefore leads to inaccurate detection. Our previous research was conducted in order to obtain the labeled compound of 99mTc-DTPA-Ketoconazole with a high radiochemical purity (98.40 ± 0.86%). Moreover, the in-vitro assays showed that 99mTc-DTPA-Ketoconazole can potentially bind to Candida albicans. On the other hand, in clinical routine use, diagnostic kit should be safe for the patients. Consequently, this research was conducted to determine the biological safety parameters of 99mTc-DTPA-Ketoconazole on the animal study, including single dose and acute toxicity test, sterility, and apirogenicity test. The results showed that both the single dose at 34.6 μCi and dose until 149 times of the single dose did not stimulate the toxic response to the animals. In addition, the sterility data revealed that there was no microbial growth after 7 days of incubation at 37°C as well as fungal growth after 14 days of incubation at 25°C. Furthermore, the apirogenicity test using rabbits revealed that there was no increase in temperature more than 0.6°C for each animal and not more than 1.5°C of total increase of temperature for all the animals. It is concluded that the 99mTc-DTPA-Ketoconazole is satisfy the requirements of biological safety of a radiopharmaceutical and therefore was acceptable for fungal detection in nuclear medicine.